An Entrepreneurial Ecosystem Doesn't Happen By Chance – The Role of RRA LUR in the Development of the Region - Marinčič, Dejan; Madjar, Lilijana; Marič, Miha (Izboljševanje podjetniške izkušnje s pomočjo podpornega okolja v Ljubljanski urbani regiji, 2025)
The Regional Development Agency of the Ljubljana Urban Region (RRA LUR) is the central development institution, established in 2001, which operates as a public institute for promoting balanced development in Slovenia's economically and demographically strongest region. In accordance with national legislation and European guidelines, it acts as a key link between the 25 municipalities, the state, and the European Union. Its central task is the preparation and implementation of fundamental strategic documents, such as the Regional Development Programme (RDP), the Regional Spatial Plan (RSP), and the Regional Sustainable Urban Mobility Plan (RSUMP), as well as acquiring EU funds and coordinating and executing development projects, which are mostly co-financed by European cohesion funds. The Agency strategically focuses on key areas such as sustainable mobility, the circular economy, promoting entrepreneurship and innovation, rural development, and the preservation of nature and culture. Through successful projects, such as the entrepreneurial programme »Enterprisingly Tackling Challenges in the Ljubljana Urban Region« (PONI LUR) and the Regional Centre for Creative Economy (RCKE), and through active participation in international networks (EURADA and AER), it significantly strengthens the region's innovation capacities, international recognition, and quality of life, following the motto »Connected for Development«.